Synergy of visible-light responsive photocatalytic materials and device engineering for energy and environment: Minireview on hydrogen production and water decontamination - Jiménez Calvo, Pablo (Materials Today Catalysis, 2024)
Accelerated advances in photocatalysis demand alignment with a well-defined Technology Readiness Levels (TRLs) roadmap to overcome bottlenecks and attain TRLs of 3 or beyond. This minireview highlights the key components for the development of device technology for photocatalytic hydrogen production, focusing on visible-light responsive catalysts and lab-scale setups. Two main aspects are critically discussed: modifications in semiconductor-based materials and progress in device engineering design. In the first section, the emphasis is on two specific energy materials: visible-light active carbon nitrides (CN) and the established benchmark titanium dioxide (TiO2). Examples of both CN and TiO2 modified by heteroatom doping, semiconductor heterojunction, metal Schottky junction, pre- and post-thermal treatments are showcased. Furthermore, Imogolite nanotubes are introduced as evolving 1D nanostructured nanoreactors for energetic photoelectrocatalysis. In the second section, the emphasis is on two types of laboratory batch photoreactors tailored for hydrogen production. Their main features are critically discussed in terms of their impact on the overall photonic, heat, and mass profiles. Moreover, a continuous flow water disinfection system is introduced as promising environmental technology. The objective to showcase these devices is to underscore the significance of advancing TRLs from 3 to 4–6. A few perspectives, routes, and challenges on visible-light absorbers and photoreactors devices are stated. Research trends are included to stay update with the latest advances in engineering and materials, specifically polyheptazine imides, computational modeling, machine learning, biomass conversion, single-atom catalysis, operando characterization, and the use of sea and wastewater for solar liquid fuels. This mini-review succinctly updates experts and non-experts on the author's recent works.<br
Keywords: Technological Readiness; Level roadmap; Visible light absorber; Photocatalysis; Hydrogen; Carbon nitrides